Semantic Web programming - Hebeler, John; Fisher, Matthew; Blace, Ryan; Perez-Lopez, Andrew (Wiley Publishing, Inc., 2009)
The first book to go beyond the general concepts of semantic Web programming to show how to actually build practical, real-world semantic Web applications The next major advance in the Web Web 3.